A Comparison of 2 Intravenous Lipid Emulsions: Interim Analysis of a Randomized Controlled Trial. (August 2014) - Nehra, Deepika; Fallon, Erica M.; Potemkin, Alexis K.; Voss, Stephan D.; Mitchell, Paul D.; Valim, Clarissa; Belfort, Mandy B.; Bellinger, David C.; Duggan, Christopher; Gura, Kathleen M.; Puder, Mark
Objective . To assess the safety and efficacy of a fish oil–based intravenous fat emulsion (FIFE) in reducing the incidence of cholestasis in neonates compared with the traditional soybean oil–based intravenous fat emulsion (SIFE). Methods . A double-blind randomized controlled trial was conducted. Nineteen neonates were enrolled (10 SIFE; 9 FIFE). Nutrition assessments and laboratory studies were serially obtained for the duration of PN support or until 6 months' corrected gestational age. Neurodevelopmental outcomes were assessed at 6 and 24 months' corrected age. Results . There were no differences between groups in demographic characteristics, with an overall median age of 2 days, gestational age of 36 weeks, and birth weight of 2410 g. There were no differences between groups in baseline laboratory values other than alkaline phosphatase (lower in the FIFE group) or in the duration of parenteral nutrition (PN), amount of enteral intake, or the number of operative procedures. The incidence of cholestasis among enrolled patients was significantly lower than expected, resulting in early study termination and an inability to assess for differences in the incidence of cholestasis. The FIFE was associated with no increased risk of growth impairment, coagulopathy, infectious complications, hypertriglyceridemia, or adverse neurodevelopmental outcomes. No patient developed essential fatty acid deficiency. Conclusion . The FIFE at 1 g/kg/d was well tolerated in the neonates recruited for this study. Given the necessary early termination of this study, a follow-up trial with revised eligibility criteria is necessary to determine whether the provision of FIFE decreases the incidence of PN-cholestasis compared with the traditional SIFE.